Profil Kompetensi Abad 21: Komunikasi, Kreativitas, Kolaborasi, Berpikir Kritis Pada Calon Guru Biologi Profile of 21st Century Competency: Communication, Creativity, Collaboration, Critical Thinking at Prospective Biology Teachers - yokhebed, yokhebed (BIO-PEDAGOGI, 2019)
21st century competency consists of communication, creativity, collaborative, and critical thinking skills (4Cs). This study aims to determine the profile of 21st century skills (4Cs) in prospective biology teachers. The research method used was survey research. Data collection tool in the form of a questionnaire. The stratified random sampling technique was used in sampling with the number of respondents 120 students of the biology education year 2018/2019. The results of the study show that the 21st century competence of prospective biology teachers is classified as moderate.